2020
DOI: 10.7120/09627286.29.3.313
|View full text |Cite
|
Sign up to set email alerts
|

Gender and job characteristics of slaughter industry personnel influence their attitudes to animal welfare

Abstract: The aim of this study was to gain an understanding of the attitudes that those involved in the slaughter industry have towards animal welfare and animal welfare aspects of their work, and also to investigate if gender or characteristics of employment (eg previous training, role and experience) influence such views. A paper questionnaire consisting of 20 Likert items regarding either animal welfare or working in the slaughter industry and seven questions designed to gather information on participant gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…The overall attitudes and affective attitudes of women were found to be more positive than men. This is consistent with Heleski et al ( 2004 ), Kupsala et al ( 2015 ), and Wigham et al ( 2020 ). Generally, women are more emotional than men and are more likely to generate emotional associations and emotional expressions; hence, the female public expresses more empathy for farm animals (Lutz, 2016 ; Mazas and Fernandez-Manzanal, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The overall attitudes and affective attitudes of women were found to be more positive than men. This is consistent with Heleski et al ( 2004 ), Kupsala et al ( 2015 ), and Wigham et al ( 2020 ). Generally, women are more emotional than men and are more likely to generate emotional associations and emotional expressions; hence, the female public expresses more empathy for farm animals (Lutz, 2016 ; Mazas and Fernandez-Manzanal, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…The influence of demographic characteristics on attitude has been explored in previous studies. (1) Gender: Heleski et al ( 2004 ), Kupsala et al ( 2015 ), and Wigham et al ( 2020 ) found that women's attitudes toward farm animal welfare were more positive than men's. (2) Age: Kupsala et al ( 2015 ) showed that young people expressed more positive attitudes toward farm animal welfare than older people.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The final category of interaction involves employees working on animals as commodities, where animals serve as integrated components of the supply chain in the process of production or experimentation (Clarke & Knights, 2022;Koch & Ulver, 2022;Magri et al, 2021). The category is dominated by farmers (Ceccato, Lundqvist, Abraham, Göransson, & Svennefelt, 2022;Medaas et al, 2021), stock people (Losada-Espinosa et al, 2020), and abattoir workers (McLoughlin, 2019) but also includes scientists in research laboratories that conduct animal testing (Ferrara et al, 2022;Hobson-West, 2012;Wigham, Grist, Mullan, Wotton, & Butterworth, 2020). Of note, this work constitutes an exponentially greater portion of employee-animal interactions and the economy than the other three combined.…”
Section: Working On Animals As Commoditiesmentioning
confidence: 99%
“…Prior research points to overwhelming work demands, such as the pressure of production, time constraints, or poor facilities, as factors that lead to high rates of animal abuse in these industries (Grandin, 1988). How these employees treat the animals has also been linked to several attitudes and personality traits (Grandin, 1988;Wigham et al, 2020). Stock people who hold negative beliefs toward animals, possess less concern for animal welfare, or rate high in neuroticism tend to assert more force and abuse when handling animals (Losada-Espinosa et al, 2020).…”
Section: Working On Animals As Commoditiesmentioning
confidence: 99%
See 1 more Smart Citation